Role of neuronal guidance cues in the pathophysiology of obesity: A peripher-al and central overview - Inoue, Daniela S. [UNESP]; Bin Maideen, Mohammad F.; Jiménez-Maldonado, Alberto; Lira, Fábio S. [UNESP] (Bentham Science Publishers, 2021)
Obesity is associated with an exacerbated synthesis and secretion of several molecules, which culmi-nates in chronic low-grade inflammation and insulin resistance. Such conditions affect molecular and physiolog-ical responses of several organs and, if not resolved, predispose the obese patients to other diseases such as Type 2 diabetes, atherosclerosis, cancer, neural injuries, and cognitive impairments. A microenvironment with an excess of pro-inflammatory cytokines released by different cells, including immune and adipose cells lead to metabolic and non-metabolic diseases during obesity. In this context, the role of neuronal guidance cues named netrin, semaphorin and ephrin is novel. Specifically, the available literature indicates that besides their classic role as molecules that guide the axon to its target site, the neuronal guidance cues exhibit immunomodulatory functions from adipose tissue to the neural environment. In the current narrative review, we discuss the partici-pation of the neuronal guidance cues on the physiology and pathophysiology of obesity. We also discuss the feedback loop of obesity on the netrin, semaphorin and ephrin functions that impair the structure and function of the brain. The integrative view of the neuronal guidance cues can be relevant in designing new treatments focus on attenuating metabolic and immune disorders in obese patients and reduce the risk of acquiring diseases such as Type 2 diabetes, atherosclerosis, cancer, and neural injuries.
Keywords: Cell adhesion; Cell migration; Eph receptors; Hippocampus; Neuropilins; UNC5B